Ländliche Neusiedlung in Dänemark vom Ende des 19. Jahrhunderts bis zur Gegenwart - Helmer Pederson, Erik (ERDKUNDE, 1986)
Around 1880 nearly 75 percent of the Danish area had been cultivated. Of the rest 14 percent could be counted as moor and heath lands and therefore subject to eventual cultivation.In the last decades of the last century heath reclamation therefore began on a large scale in Jutland especially. The result was that around 1950 only 280,000 hectares remained of the original moor and heath lands in Denmark. Consequently the figures of farms and farm population rose considerably during the same period. Far more intense methods of tilling the land then made it possible not only to increase the production on existing Danish farms, but also to view the small holdings as a secure basis of a family's income. The Small Holdings Act of 1899 then provided for state loans to suitable applicants and right up to 1919 more than 9,000 state small holdings were created, not least in the heath areas of Jutland. In1919 the Small Holdings Act was supplemented with an act of conversion of entailed estates into fee simple. It forced the great landlords to give up 20-30 percent of their land for the creating of state small holdings, to be let to the applicants at economic rents. Up to 1967 more than 30,000 small-holdings have thus been created in Denmark, but only comprising one percent of the agricultural area. Land reclamation in the true sense of the word has never been very significant in Denmark. Perhaps 20,000 hectares have been reclaimed in this century through diking, drain aging and enpoldering. Some importance has been attached to the draining of the Danish marshes in the southern part of Jutland, to some extent co-ordinated with the corre sponding reclamation work in the northern part of Ger many. In most cases the reclaimed lands have been con veyed to already existing farms and not used as a basis for creating new holdings. In point of fact the tidal wave has now turned in Denmark's official land policies. The farms are now being put together into bigger units and people are leaving farming in great numbers. From 206,000 holdings the number now has dropped to circa 95,000 and only 67 percent of the area are being tilled. Bigger farms and specialized production are the key words of modern Danish agriculture.